2010
DOI: 10.1002/ejoc.201000239
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Ionic Liquids Bearing O‐Silylated α,α‐Diphenyl (S)‐ or (R)‐Prolinol Units: Recoverable Organocatalysts for Asymmetric Michael Addition of Nitroalkanes to α,β‐Enals

Abstract: Chiral ionic liquids bearing O-silylated α,α-diphenyl (S)-or (R)-prolinol units tagged to the imidazolium cation were synthesized and their activity as catalysts in the Michael addition of nitroalkanes to α,β-unsaturated aldehydes was evaluated. Respective (S) or (R) adducts were obtained in the reactions in high yields (up to 95 %) and with high enantio-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 88 publications
1
36
0
Order By: Relevance
“…The enantioselectivity was determined by HPLC analysis (77% ee, Daicel CHIRALPAK AD-H, 5% isopropanol/hexane, 1.0 mL/min, 229 nm; t r (major enantiomer) = 18. Spectroscopic data of γ-nitroketones 4 are in agreement with published data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. …”
Section: Typical Procedures For the Michael Addition Of Nitroalkanes Tsupporting
confidence: 84%
See 1 more Smart Citation
“…The enantioselectivity was determined by HPLC analysis (77% ee, Daicel CHIRALPAK AD-H, 5% isopropanol/hexane, 1.0 mL/min, 229 nm; t r (major enantiomer) = 18. Spectroscopic data of γ-nitroketones 4 are in agreement with published data [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. …”
Section: Typical Procedures For the Michael Addition Of Nitroalkanes Tsupporting
confidence: 84%
“…As pioneering works in organocatalytic asymmetric Michael addition of carbon nucleophiles to α,β-unsaturated carbonyl compounds, Yamaguchi's group reported that Michael addition of malonates to enones could be catalyzed by a proline alkali metal salt [6][7][8][9][10][11][12]. They later succeeded in the asymmetric Michael addition of nitroalkanes to enones using a proline rubidium salt-catalyst [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. We recently reported that an O-silylated L-serine lithium salt was an effective catalyst for asymmetric Michael addition of malonates to enones to give various 1,5-ketoesters in good yields with high enantioselectivity [33].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (IL) have shown interesting ability as phase tags for organocatalysts. [6][7][8][9][10][11][12][13][14][15] Ionic liquid tagged catalysts can be tuned to attain a required physical property, such as solubility, or compatibility with the reaction medium and thermal stability. 16 In this way improved recovery and recycling and sometimes even better catalytic activity can be attained.…”
Section: Introductionmentioning
confidence: 99%
“…16 In this way improved recovery and recycling and sometimes even better catalytic activity can be attained. [17][18][19]14 Accordingly, we envisaged that a properly functionalized ionic liquid tag can render TADDOLs novel properties and improve their usefulness as organocatalysts. Immobilizing TADDOL catalysts with ionic liquids has the potential to render the TADDOLs tuneable solubility for working under homogeneous conditions, without diminishing their catalytic activity or their amount of catalyst loading, unlike TADDOLs immobilized on solid supports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation